Effects of L-Carnitine and Fish Oil Supplementations in the Diet to Digestibility of Crude Fat, Fiber, and Feed Conversion in Native Chicken - Sudibya Sudibya; Septi Handayani; Putri Purba Yunendra; Sukaryo Sukaryo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
The aim of this study was to find out the effect of L-carnitine and fish oils on crude fat and fiber digestibilities, and feed conversion in native chicken. This study used 100 Kampung chickens aged 20 weeks. Feed treatments were divided into four groups consisted of basal diet, basal diet supplemented by L-carnitine, basal diet supplemented by L-carnitine and Tuna fish oil, and basal diet supplemented by L-carnitine and Lemuru fish oil. The data observed in this study were crude fat consumption and digestibility, crude fiber consumption and digestibility, feed consumption, and feed conversion ratio (FCR). Those data were analyzed using analysis of variance and an orthogonal contrast test was applied to distinguish among groups. Statistical analysis showed that highly significant effects of L-carnitine and fish oils supplementation on crude fat and fiber consumptions, and crude fat digestibility were found in this study (P<0.01). Moreover, L-carnitine and fish oils supplementation in the diet significantly affected crude fiber digestibility, feed consumption, and FCR (P<0.05). In conclusion, supplementation of Tuna and Lemuru fish oils until 4% containing 30 ppm L-carnitine improved crude fat consumption, digestibilities of crude fat and fiber, and decreased crude fiber digestibility, feed consumption, and FCR.